The Use of Scrapbook to Increase Knowledge and Preparedness of Elementary School Students in Facing a Tornado Disaster : Original Article - Hidayati, Nur; Jamilah, Mar'atun; Hanafi, Aprelia Afidatul (Babali Publisher, 2024)
Introduction: Tornado is the second most common disaster in Lamongan after floods. Elementary school students are one of the groups vulnerable to this kind of disaster. The purpose of the study was to determine the effect of Scrapbook on the knowledge and preparedness of elementary school students in dealing with tornado. Method: This research used quasi-experimental (nonequivalent control group) design with a total sample of 131 students divided into 2 groups, the intervention group (47) and the control group (84), were selected using total sampling. This study was conducted at Muhammadiyah Plus Maduran Elementary School and Bedahan Babat Public Elementary School in March 2024. The intervention group was given education using scrapbook, while the control group was not given any education. The data were collected through knowledge and preparedness questionnaires, then they were analyzed using Wilcoxon test, Paired t-test, and Mann-Whitney (α≤0.05). Result. The results indicated that there was a difference in knowledge and preparedness of students before and after treatment in the intervention group (p=0.001; p=0.001) while there was a difference in knowledge and preparedness of students before and after treatment in the control group (p=0.317; p=0.083). There was a difference in students’ post-test knowledge and preparedness in dealing with tornado disasters between the intervention group and the control group (p=0.001; p=0.001). Conclusion. Scrapbook is proven to significantly increase the knowledge and preparedness of elementary school students in dealing with tornado. The future researchers can develop Scrapbook into digital media so that it is accessible to children through gadgets.